STRATEGIC MANAGEMENT IN PUBLIC SERVICES ORGANIZATIONS concepts, schools and... contemporary issues. - Ferlie, Ewan, 1956-; Ongaro, Edoardo ([S.l.] : ROUTLEDGE, 2022)
Strategic Management in Public Services Organizations takes a comparative and international view on the appropriate use of strategic management models that are affecting the way public services organizations are managed. In an era of New and post New Public Management reforms, public managers at all levels are expected to respond to these new approaches,which profoundly affect their work practices, skills, and knowledge bases. Choosing a promising strategic management model and implementing it in a way that works for the organization or inter-organizational network in question also depends on an understanding of local politico-administrative and cultural contexts: this book helps the readers identify how to successfully tailor strategic management approaches to their specific circumstances and needs. This second edition builds upon the successes of the well-received first edition. Thoroughly updated to help public managers meet the challenges of a new decade, it has a refreshed collection of mini-cases and now includes chapter summaries. It also includes a new chapter on collaborative strategy and co-creation, in response to the growth of interest in more open forms of public policymaking. This is an advanced textbook aimed at the postgraduate level, particularly students on MPAs and MBAs with a public sector option or MScs in public policy and public management.
Revised edition of the authors' Strategic management in public services organizations, 2015.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Nonprofit Organizations & Charities; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Government & Business; Public administration; Strategic planning; Administrative agencies -- Management